Community Empowerment Program Based on Strengthening Entrepreneurial Competencies and Character - Famimsyina, Widialasri; Yulastri, Asmar; Ernawati , Ernawati; Yuliana , Yuliana (LP2M INSURI Ponorogo, 2025)
One of the potentials of Nagari Maninjau is the potential of the region and the existence of its MSMEs. However, understanding of the competencies and characteristics of MSME entrepreneurs is still relatively low. In this era of global economic competition, a need to strengthen entrepreneurial competencies and characters. The purpose of this community service is to provide education on the urgency of strengthening entrepreneurial competencies and characters. The method used in this service is participatory action research (PAR) for a full month at the service partner of Nagari Maninjau, Agam. Direct community involvement is seen in several community service activity programs, including, as many as 20 business actors and MSMEs participated in training activities. The results of this service are increased confidence in running a business, several MSME products have been able to carry out digital promotions, improved sales strategies and customer service.